2005
DOI: 10.3354/meps299007
|View full text |Cite
|
Sign up to set email alerts
|

Continuity in the photosynthetic production of dissolved organic carbon from eutrophic to oligotrophic waters

Abstract: , PER was relatively constant at ~20%, and integrated DOCp could be predicted from integrated POCp with the equation: log (DOCp) = 0.96 × log (POCp) -0.51 (r 2 = 0.90, n = 35, p < 0.001). KEY WORDS: Phytoplankton · Dissolved organic carbon · Oligotrophic conditions · Celtic SeaResale or republication not permitted without written consent of the publisher Mar Ecol Prog Ser 299: 7-17, 2005 zone does not allow one to conclude unequivocally which environmental factors control the vertical variability in the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 24 publications
7
49
1
3
Order By: Relevance
“…Estimates on the percent of primary production released as DOC vary largely among studies. Although some studies report a percentage of excretion constant across trophic gradients (Maranon et al, 2005); both laboratory (Myklestadt, 1995;Obernosterer and Herndl, 1995) and field studies (Teira et al, 2001;Moran et al, 2002;Fernández et al, 2004), indicate an increase of the percent of primary production released as DOC in nutrient-limited environments. In the South Pacific Gyre primary production was strongly limited by nitrogen (Bonnet et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates on the percent of primary production released as DOC vary largely among studies. Although some studies report a percentage of excretion constant across trophic gradients (Maranon et al, 2005); both laboratory (Myklestadt, 1995;Obernosterer and Herndl, 1995) and field studies (Teira et al, 2001;Moran et al, 2002;Fernández et al, 2004), indicate an increase of the percent of primary production released as DOC in nutrient-limited environments. In the South Pacific Gyre primary production was strongly limited by nitrogen (Bonnet et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baines & Pace (1991) concluded that DOM release is constrained by the total availability of photosynthates, rather than phytoplankton biomass, and therefore active processes are more important than diffusion. However, constant PER throughout the water column, which only increased at very low light conditions, led to the conclusion that DOC release was the result of passive diffusion rather than photosynthetic overflow (Marañón et al, 2004(Marañón et al, , 2005. The passive diffusion model implies that a population dominated by small cells should have a higher PER than populations of larger cells.…”
Section: Dom Release By Passive Diffusion Across the Cell Membranementioning
confidence: 99%
“…Total primary production (TPP) can be divided into particulate primary production (PPP) and dissolved primary production (DPP). PER is simply DPP/TPP × 100 (Marañón et al, 2005;Morán et al, 2006). While PER is a useful parameter to understand the physiology of phytoplankton, it is not as useful as the absolute measures of carbon flux for understanding the biogeochemistry of ecosystems.…”
Section: Production Rates Of Dom By Phytoplanktonmentioning
confidence: 99%
“…Because the methodological problems associated with 24-h incubation experiments affect both carbon (Moutin et al 1999, Maranon et al 2005 and phosphate (Nalewajko andGarside 1983, Harrison andHarris 1986) uptake measurements, we decided to measure hourly rates, at noon. Losses remain negligible for short-term incubations (Nalewajko and Garside 1983, Harrison and Harris 1986, Moutin et al 1999, Maranon et al 2005 and consequently, these rates are close to gross rates.…”
Section: Discussionmentioning
confidence: 99%